Trigeminal fistula treated by combined transvenous and transarterial embolisation - S. Geibprasert (2018)
Trigeminal cavernous fistulae are rare, compared to other types of carotid-cavernous fistulae with only about 17 examples previously reported in English literature. The aetiology can be either post-traumatic or spontaneous, and in the latter group either due to a ruptured trigeminal aneurysm or postulated intrinsic weakness of the artery itself. The treatment goal is to close the fistula while preserving the parent artery and this can be done either by surgical or endovascular methods. We present a 35-year-old woman with a spontaneous trigeminal fistula treated by combined trans-venous and trans-arterial embolisation. © 2008 Springer-Verlag.